2010
DOI: 10.1007/s11325-010-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-tonsillectomy and rapid maxillary distraction in pre-pubertal children, a pilot study

Abstract: Introduction When both narrow maxilla and moderately enlarged tonsils are present in children with obstructive sleep apnea, the decision of which treatment to do first is unclear. A preliminary randomized study was done to perform a power analysis and determine the number of subjects necessary to have an appropriate response. Thirtyone children, 14 boys, diagnosed with OSA based on clinical symptoms and polysomnography (PSG) findings had presence of both narrow maxillary complex and enlarged tonsils. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
30

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 10 publications
0
95
0
30
Order By: Relevance
“…Recently, a randomized study performed in Caucasian prepubertal children with OSA mostly recruited from an otolaryngological practice showed that many children would benefit from both otolaryngological and orthodontic treatment; in that report, one out of all the children treated initially with orthodontics maneuvers did not need further otolaryngological treatment [7]. Our investigation looks further at this interaction between otolaryngologic and orthodontic treatment in OSA.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, a randomized study performed in Caucasian prepubertal children with OSA mostly recruited from an otolaryngological practice showed that many children would benefit from both otolaryngological and orthodontic treatment; in that report, one out of all the children treated initially with orthodontics maneuvers did not need further otolaryngological treatment [7]. Our investigation looks further at this interaction between otolaryngologic and orthodontic treatment in OSA.…”
mentioning
confidence: 76%
“…Some of these previous reports present typical cases of obstructive sleep apnea in children but without having polygraphic demonstration of SDB [20,21,22,25,26]. Investigation of the role of orthodontics in nonsyndromic OSA children has been more systematic in recent times [6,7,14,15,28]. But the first line of treatment for Review many children with OSA is still AT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta interrogante no está del todo clara y generalmente se tiende a realizar el tratamiento que ofrece el especialista a quien consulta primero el paciente. Guilleminault y cols 16 , realizaron un estudio randomizado con 31 pacientes diagnosticados de SAOS por hiperplasia adenoamigdalina con maloclusiones con indicación de ERM. Se dividieron en 2 grupos, el primer grupo fue sometido a adenoamigdalectomía seguido de ERM mientras que el segundo grupo fue tratado primero con ERM y luego adenoamigdalectomía.…”
Section: Tratamiento Del Saos Residual Posadenoamigdalectomíaunclassified
“…Such approaches, alone and in combination with adenotonsillectomy, have been published for almost a decade although numbers are quite small [29,30]. I However, despite near-normalization of sleep architecture and significantly improved AHI one year after intervention, some aspects of sleep microstructure were disturbed, suggesting incomplete response to therapy [31].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%